2008
DOI: 10.1111/j.1744-1609.2008.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of simulation on health profession students' knowledge, skills, confidence and satisfaction

Abstract: This review included participants who were pre-licensure practitioners in nursing, medicine, and rehabilitation therapy. Types of intervention(s)/phenomena of interest: Studies that evaluated the use of human physical anatomical models with or without computer support, including whole-body or part-body simulators were included. Types of outcome measures  Student outcomes included knowledge acquisition, skill performance, learner satisfaction, critical thinking, self-confidence and role identity. Search strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
87
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 28 publications
5
87
0
13
Order By: Relevance
“…This is consistent with review articles that concluded simulation sessions purportedly facilitate learning 28,29 . To optimize the experience, the authors of the present study were often able customize cases at a rural center's request, mimicking past difficult cases or addressing an area of need.…”
Section: Discussionsupporting
confidence: 76%
“…This is consistent with review articles that concluded simulation sessions purportedly facilitate learning 28,29 . To optimize the experience, the authors of the present study were often able customize cases at a rural center's request, mimicking past difficult cases or addressing an area of need.…”
Section: Discussionsupporting
confidence: 76%
“…Simulation is now widely utilised within the undergraduate and ongoing midwifery education contexts Laschinger et al, 2008;Skirton et al, 2011). This review has identified several issues, both positive and negative, related to the use of simulation for midwifery education.…”
Section: Discussionmentioning
confidence: 99%
“…This has been influenced by numerous factors, such as declining inpatient populations, rarity of some emergency clinical situations, safety concerns and advances in learning theory, forcing educators to move away from traditional clinical encounters to support student skill acquisition (Laschinger et al, 2008;McKenna et al, 2011). Simulation is being used in undergraduate midwifery education as a way of preparing students to practise safely; it has the potential to ensure graduate midwives are capable of assuming the full mantle of responsibilities and accountabilities of a midwife on graduation (Lake & McInnes, 2012).…”
Section: Literature Review Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include the response to obstetric emergencies, [43] the response to emergencies by nursing and medical students, [41,42] resuscitation in pediatrics by physicians and nurses, [40] or advanced cardiac life support by physicians, nurses and paramedics. [41,44] The contribution of simulation to help students make an appropriate use of the knowledge and competences [5,6,42] is something that can help to explain this link between students' self-confidence and practical assessment.…”
Section: Discussionmentioning
confidence: 99%